PENERAPAN MODEL PEMBELAJARAN MISSOURI MATHEMATICS PROJECT UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH PADA TEORI GRAF - Suryati, Ni Kadek; Putri, Ni Wayan Suardiati (Widyadari : Jurnal Pendidikan, 2019)
The purpose of this study was to determine the ability to solve mathematical problems, especially the material of graph theory and student learning interest by using learning models missouri mathematics project (MMP). This research is a qualitative research approach with the research design used is classroom action research (CAR) or classroom action research. The subjects of this study are students of class I study program of informatics engineering at STMIK STIKOM Indonesia. The method of data collection is done through observation, field notes, documentation, learning interest questionnaires and problem solving ability tests. The results of this study are the interest in student mathematics learning on graph theory on high criteria and increasing student learning outcomes in the ability to solve mathematical problems through the Missouri Mathematics Project (MMP) learning model on the subject of graph theory. This is indicated by an increase in the percentage of the average value of problem solving abilities, learning completeness, and student absorption from pre-cycle to cycle I in a row equal to16,18%, 30,00%, 16,05%. While from cycle I to cycle II to increase the percentage of the average value of problem solving skills, learning completeness, and student absorption from pre-cycle to cycle I in a row amounting to25,27%, 46,15%, 35,29%.